Peran Dinas Perikanan dalam Pemberdayaan Ekonomi Masyarakat Nelayan Pesisir di Kabupaten Deli Serdang - Nainggolan, Frans Rosaveld Hamonangan; Hartono, Budi; Adam, Adam (Mahesa Research Center, 2023)
This study aims to disclose or scientifically analyze the role and constraint factors faced by the Department of Fisheries in the economic empowerment of coastal fishing communities in Deli Serdang Regency. The research method used is the descriptive method, with a qualitative descriptive analysis technique that focuses on the process, and description of the analysis. Data collection was obtained from observation, interviews, and documentation. The research results refer to the theory of Sondang P. Siagian, namely the role of the government in development as a stabilizer, innovator, modernizer, pioneer and self-executor. The Deli Serdang Regency Fisheries Service has conducted its role in the economic empowerment of coastal fishing communities but has not provided optimal results. Obstacles faced by the Fisheries Service include the lack of number, expertise, and competence of the apparatus in the Fisheries Service in coaching and mentoring, Low participation of fishing communities in participating in training activities conducted by the Fisheries Service, Low managerial / group management abilities, Awareness, and business intention is still low. exceptionally low and budget constraints. Recommendations in this study are expected that the Fisheries Service needs to socialize the importance of expertise and ability to be able to increase competence and business opportunities, the Fisheries Service should play a more role in fostering and assisting in managerial/administrative management and group fishery facilities assets, as well as being more selective in program planning assistance to fishermen based on the priority scale of the basic needs most needed by fishermen.